2022
DOI: 10.1093/rb/rbac005
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and biological evaluation of 3D-printed calcium phosphate ceramic scaffolds with distinct macroporous geometries through digital light processing technology

Abstract: Digital light processing (DLP)-based 3D printing technique holds promise in fabricating scaffolds with high precision. Here raw calcium phosphate (CaP) powders were modified by 5.5% monoalcohol ethoxylate phosphate (MAEP) to ensure high solid loading and low viscosity. The rheological tests found that photocurable slurries composed of 50 wt % modified CaP powders and 2 wt % toners were suitable for DLP printing. Based on geometric models designed by CAD system, three printed CaP ceramics with distinct macropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Another of their studies showed that MAEP modification could convert CaP from a hydrophilic to a hydrophobic state (water contact angle increased from 0°to 80 ± 2°; Figure 6c). 111 However, the viscosity of the CaP suspension increased when the MAEP concentration exceeded 5%, and finally, a 60 wt % solid-loaded CaP suspension was prepared under the printing viscosity requirement.…”
Section: Bioactive Ceramic Suspensions For Vpmentioning
confidence: 99%
See 1 more Smart Citation
“…Another of their studies showed that MAEP modification could convert CaP from a hydrophilic to a hydrophobic state (water contact angle increased from 0°to 80 ± 2°; Figure 6c). 111 However, the viscosity of the CaP suspension increased when the MAEP concentration exceeded 5%, and finally, a 60 wt % solid-loaded CaP suspension was prepared under the printing viscosity requirement.…”
Section: Bioactive Ceramic Suspensions For Vpmentioning
confidence: 99%
“…215 However, animal experiments to verify osteogenic capacity are lacking. According to Figure 18d, Wang et al 111 produced a multilayer pore structure of macropores (>500 μm), minorpores (10 μm), and micropores (0.3−2 μm) by adding toners to the CaP suspension as a porogen. Although the porous scaffold showed good bioactivity, its osteoinductive ability was still weaker than that of the foamed scaffold (Figure 18e).…”
Section: Performance Of Vp-printed Bioactive Ceramic Bone Scaffoldsmentioning
confidence: 99%
“…In particular, the biological sealing can be improved via surface modification [ 35 , 36 ]. Unlike a porous scaffold [ 37 ], titanium and its alloys are applied as a bulk material as usual, yet still with a large amount of surfaces exposed to the tissue environment and faced with a challenge of biological sealing. Ding et al .…”
Section: The Different Sources Of Biomaterials For Tissue Regenerationmentioning
confidence: 99%
“…2B , Zhu et al . [ 37 ] compared the osteoinductive effects of various CaP ceramic scaffolds with distinct structures of cube, octet-truss, inverse face-centered cube (fcc) and foam. They found that the scaffolds with a foamlike structure showed strongest osteoinduction owing to the local high ionic microenvironment caused by some non-through holes and smaller pore diameter.…”
Section: The Different Sources Of Biomaterials For Tissue Regenerationmentioning
confidence: 99%
“…According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), porous materials can be simply classified based on their pore size. Materials with a pore size of less than 2 nm are microporous materials, including zeolites [ 1 ] and metal–organic frames (MOFs) [ 2 ], while those with a pore size larger than 50 nm are macroporous materials, with major representative materials such as aerogels [ 3 ] and porous ceramics [ 4 ]. When the pore size is between 2 nm and 50 nm, porous materials are named mesoporous materials.…”
Section: Introductionmentioning
confidence: 99%